Phylogenetic Relationship of Genus Microhyla (Amphibia, Anura) in Sunda Shelf including Sumatra, Java, Borneo, and Peninsular Malaysia as revealed by 16S rRNA mtDNA Gene Sequences - Firdaus, Anggun; Ratih, N; Karima, I; Kusuma, A T; Suastika, N M (Future Science, 2018)
Sundaland was a single large landmass during Pliocene and Pleistocene period and consisted of Java, Borneo, Sumatra, Malay-Peninsula and others smaller island. We used 26 partial DNA sequences of the mitochondrial DNA genes 16S rRNA from taxa of Microhylidae (23 genus Microhyla and 3 outgroups) from GenBank. We aligned sequences using MEGA 5 software. Phylogenetic trees were constructed using maximum parsimony (MP) and maximum likelihood (ML) with 1000 bootstraps. Our results reveal three monophyletic clades which are not supported: clade A (all Sundaland, including M. malang, M. borneensis, M. mantheyi, M. achatina, M. berdmorei, M. superciliaris, and M. palmipes); clade B (from Borneo and Malay Penisular, including M. annectens, M. perparva, and M. petrigena); and clade C (consists of outgroup species, Metaphrynella pollicaris, Chaperina fusca, and Kalophrynus heterochirus). Clade A reveal three subclades with unresolved relationship: AI (M. malang, M. borneensis, M. mantheyi, M. achatina, and M. berdmorei), AII (M. supercilliaris), and AIII (M. palmipes). Clade B reveal two well-supported subclades: BI (M. annectens) and BII (M. perparva and M. petrigena). Our results show that phylogenetic within genus Microhyla was mostly affected by species distributions. Keywords: Microhyla, phylogenetic, Sundaland